Breaking Domestic Boundaries: The Role of Affiliate Marketing in Building Productivity Among Housewives in the Digital Age - Istiqomah, Yuliani; Setiawati, Liya; Somantri, Asep (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to explore how affiliate marketing in e-commerce contributes to improving the productivity and standard of living of housewives in the digital age. Methodology: This study uses a descriptive qualitative approach with in-depth interviews with eight informants who are housewives actively participating in affiliate marketing programmes. Data collection techniques include semi-structured interviews, social media observation, and digital documentation, analysed using the interactive model of Miles and Huberman. Results: The findings reveal that affiliate marketing provides flexible income opportunities and has a positive impact on the social and psychological aspects of housewives. Platforms such as TikTok and Shopee are the primary media for affiliate promotion. Findings: This study reveals that affiliate marketing not only serves as an economic tool but also as a means of empowering women through increased self-confidence, productivity, and social recognition. Novelty: This study offers a new perspective by examining affiliate marketing as a medium for empowering housewives, not merely as a digital marketing strategy. Originality: The uniqueness of this study lies in its multidimensional approach, which combines economic, social, and psychological aspects in the context of housewives' participation in the digital space. Conclusion: Affiliate marketing contributes significantly to the empowerment of housewives in the digital age, although challenges such as digital literacy and dependence on platform algorithms remain obstacles.